Applying single-image super-resolution for the enhancement of deep-water bathymetry. Issue 10 (October 2019) - Nock, Kristen; Bonanno, David; Elmore, Paul; Smith, Leslie; Ferrini, Vicki; Petry, Fred
Abstract: We present research using single-image super-resolution (SISR) algorithms to enhance knowledge of the seafloor using the 1-minute GEBCO 2014 grid when 100m grids from high-resolution sonar systems are available for training. We performed numerical experiments of x15 upscaling along three midocean ridge areas in the Eastern Pacific Ocean. We show that four SISR algorithms can enhance this low-resolution knowledge of bathymetry versus bicubic or Splines-In-Tension algorithms through upscaling under these conditions: 1) rough topography is present in both training and testing areas and 2) the range of depths and features in the training area contains the range of depths in the enhancement area. We quantitatively judged successful SISR enhancement versus bicubic interpolation when Student's hypothesis testing show significant improvement of the root-mean squared error (RMSE) between upscaled bathymetry and 100m gridded ground-truth bathymetry at p < 0 . 05. In addition, we found evidence that random forest based SISR methods may provide more robust enhancements versus non-forest based SISR algorithms. Abstract : Computer Science; Earth sciences; single-image super-resolution; upscaling; bathymetry